A comparative study between males and females in the some cognitive abilities sense-motor of pre-school children aged (5-6) years - جاقمة , رمضان; بن حاج الطاهر , عبد القادر (Journal of Sport Science Technology and Physical Activities, 2021)
The Object of the study aims to identify the difference between males and females in the some cognitive abilities sense-motor of pre-school children. for this purpose, we used the comparative descriptive method On a sample composed of 2O boys and 20 girls Chosen intentionaly, and for data collection, we used the Haywood scale of cognitive abilities sense-motor, After collecting the results and having treated them statistically, we conclude there are no significant difference between males and females in the cognitive abilities sense-motor under considiration